Careering towards change. Issue 2 (13th March 2017) - Linacre, Simon
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoints practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: It is a truth universally acknowledged that an individual in possession of a good degree will want a job. While this has been a constant for centuries, not withstanding the huge rises globally in access to higher education, recent times have seen significant changes not just in the job market itself, but in the very essence of what having a job means. Twenty to thirty years ago, having a job would usually entail an apprenticeship or graduate trainee position, followed by a gradual rise through the ranks to management, senior management and if you were lucky, the c-suite and a place at the top table of an organization. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.